Towards the discovery of novel genetic component involved in stress resistance in Arabidopsis thaliana. Issue 3 (18th October 2013) - Juraniec, Michal; Lequeux, Hélène; Hermans, Christian; Willems, Glenda; Nordborg, Magnus; Schneeberger, Korbinian; Salis, Pietrino; Vromant, Maud; Lutts, Stanley; Verbruggen, Nathalie
Summary: The exposure of plants to high concentrations of trace metallic elements such as copper involves a remodeling of the root system, characterized by a primary root growth inhibition and an increase in the lateral root density. These characteristics constitute easy and suitable markers for screening mutants altered in their response to copper excess. A forward genetic approach was undertaken in order to discover novel genetic factors involved in the response to copper excess. A Cu 2+ ‐sensitive mutant named copper modified resistance1 ( cmr1 ) was isolated and a causative mutation in the CMR1 gene was identified by using positional cloning and next‐generation sequencing. CMR1 encodes a plant‐specific protein of unknown function. The analysis of the cmr1 mutant indicates that the CMR1 protein is required for optimal growth under normal conditions and has an essential role in the stress response. Impairment of the CMR1 activity alters root growth through aberrant activity of the root meristem, and modifies potassium concentration and hormonal balance (ethylene production and auxin accumulation). Our data support a putative role for CMR1 in cell division regulation and meristem maintenance. Research on the role of CMR1 will contribute to the understanding of the plasticity of plants in response to changing environments.